A Igualdade e a Liberdade na Democracia segundo Tocqueville - Cunha, Gustavo Caetano Pozzi da (Universidade Federal de São Carlos, 2019)
In this dissertation, which has as theoretical support the political philosophy of Alexis de Tocqueville, an analysis is made of the concepts of equality and liberty, as conditions for the existence of democracy in America, considering the socio-political-economic context, in which the author observed them in the American society of his time, comparing them with the development of democracy in Europe, especially in France, post-revolution. It has, as one of the challenges to be overcome, the possibility of reconciling equality and liberty for the consolidation of a democratic state. It is a bibliographical research of the concepts elaborated by the philosopher, provoking debates and shedding light for the understanding of the current stage of democracy in Brazil and in the world.
Equality and Freedom in Democracy according to Tocqueville
Keywords: Democracia; Igualdade de condições; Liberdade; Cidadania; Democracy; Equality of conditions; Liberty; Citizenship; CIENCIAS HUMANAS